Does Predisposition Toward Disgust Affect Emotional Response to Political Leaders? Evidence from the 2012 U.S. Presidential Election. (29th July 2019) - Stewart, Patrick A.; George, Jamilah R.; Adams, Thomas
Abstract : Objective: We explore the effects of trait disgust sensitivity and induced disgust on emotional response to political leaders. We assert that disgust sensitivity, especially in response to pathogen‐based stimuli (e.g., insects, feces, and vomit), will affect an individual's interaction with his or her political environment, including political leaders. Methods: We analyze the effect of individual predispositions in response to stimuli indicating the presence of pathogens on emotional response to President Barack Obama, as well as his Republican challenger during the 2012 election, Mitt Romney. Study 1 utilizes cross‐sectional data to determine how disgust sensitivity relates to how President Obama made respondents feel. Study 2 analyzes experimental data considering the effect of a disgusting odorant (butyric acid) on emotional response to Obama and Romney. Results: Findings suggest disgust plays an important role in emotional response to political leaders both through trait sensitivity and when induced and it is particularly relevant to emotional responses to President Obama. Conclusions: Disgust, both as a trait sensitivity and as experimentally induced by an odorant, influences emotional response to the political environment, including high‐profile political leaders.